2012
DOI: 10.1111/j.1551-2916.2012.05392.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Syntheses and Structural Phase Transitions of AgNbO3

Abstract: The phase‐pure AgNbO3 has been prepared through the hydrothermal reactions of NH4HF2, Ag2O, and Nb2O5. The room‐temperature powder X‐ray diffraction analysis reveals that it crystallizes in orthorhombic perovskite lattice with a space group of Pmc21 and cell parameters a = 15.6999(9), b = 5.5521(1), and c = 5.5830(1) Å. The temperatures, pH values, and times play crucial roles in obtaining phase‐pure silver niobate. The structural phase transitions were observed at 813 K from cubic to tetrahedral phase and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 24 publications
(51 reference statements)
1
15
0
1
Order By: Relevance
“…The AgNbO 3 powders were prepared by the hydrothermal method, as we reported previously. 11 The prepared powders were ground, pressed into pellets, and then annealed at 1353 K in a flowing O 2 atmosphere for 8 h. The X-ray diffraction data for the sintered powder were collected on Rigaku D/Max 2500V/Pc X-ray diffractometer (Tokyo, Japan) with Cuk a radiation (k = 1.5418 A) at 50 kV and 200 mA at room temperature. The morphology of the sintered pellet was checked with a JEOL JMS-6480LV scanning electron microscope (SEM; Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The AgNbO 3 powders were prepared by the hydrothermal method, as we reported previously. 11 The prepared powders were ground, pressed into pellets, and then annealed at 1353 K in a flowing O 2 atmosphere for 8 h. The X-ray diffraction data for the sintered powder were collected on Rigaku D/Max 2500V/Pc X-ray diffractometer (Tokyo, Japan) with Cuk a radiation (k = 1.5418 A) at 50 kV and 200 mA at room temperature. The morphology of the sintered pellet was checked with a JEOL JMS-6480LV scanning electron microscope (SEM; Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…However, some early reports have shown that the M1 phase has a centro‐symmetric space group Pbcm which does not allow the existence of a spontaneous polarization at room temperature . Later, neutron and synchrotron powder diffractions at room temperature revealed that the M1 phase actually belongs to a non‐centrosymmetric space group Pmc 2 1 . Accordingly, the M1 phase should be ferroelectrically active along the c direction .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other perovskite niobates, AgNbO 3 undergoes a complex series of phase transitions as a function of temperature, pressure, and electric field, and many details about the subtly different ferroelectric (FE) and antiferroelectric (AFE) states are still not well understood, prompting a number of experimental and theoretical studies in recent years [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Base on the ICP analysis and XRD pattern, the prepared sample is consistent with that reported previously. 3 In our experiments, 2 the prepared powders were ground, pressed into pellets, and then annealed at 1353 K in a flowing O 2 atmosphere for 8 h. To further avoid any contamination of moisture during the dielectric and the DSC measurements, the pellets and the powders were preheated to 473 K with an annealing time of 2 h, and then cooled to room temperature prior to the measurements. As mentioned in our article ( Fig.…”
mentioning
confidence: 99%